Analisis Pengaruh Literasi Keuangan, Pendapatan, Dan Gaya Hidup Terhadap Pengelolaan Keuangan Para Pekerja Di Kabupaten Bekasi - Yuliani, Rini; Fahamsyah, Mohammad Hatta (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Financial management is an important aspect in meeting human life needs in order to achieve success in managing finances, so as to prevent financial problems from occurring in the future.  People often experience problems in managing finances, especially workers. Problems that often occur among workers are lack of financial literacy, increasing costs of living and unstable income, so this becomes a challenge for workers in determining good financial management strategies in the future. . This research aims to examine the influence of financial literacy, income and lifestyle on the financial management of workers in Bekasi Regency, West Java. The research method used was quantitative with a sample size of 100 workers who were still productive in Bekasi Regency. The data collection technique used was a questionnaire. The sampling method uses probability sampling with simple random sampling technique. The analytical methods used are validity test, reliability test, t test and R-square. The test tool used is SmartPLS 4.1.0.3 with the PLS-SEM (Partial Least Squares-Structural Equation Modeling) analysis method. The results of the research show that financial literacy has a significant positive effect on financial management, income has a significant positive effect on financial management and lifestyle has a significant positive effect on financial management on the financial management of workers in Bekasi Regency.